Analysing the optical network unit power consumption in the 10 GB‐capable passive optical network systems. Issue 3 (1st May 2016) - Sarigiannidis, Panagiotis; Louta, Malamati; Papadimitriou, Georgios; Theologou, Michael
Abstract : The standardisation of the 10 GB‐capable passive optical network (XG‐PON) system is accompanied by a rigorous set of recommendations. Power reduction in XG‐PONs is considered a quite important topic by the telecommunication standardisation sector (ITU‐T), thus, with importance of energy saving, XG‐PON recommendation describes power management processes in detail. The core power management process comprises distinct states representing the desired power management transitions, while two modes: namely, the doze and the cyclic sleep mode, are defined. This study provides an analytical model for power consumption computation of an optical network unit (ONU), assuming that the two modes are enabled in the ONU operation. The presented analytical findings are verified by conducting extensive simulation experiments. Concurrently, the average time spent on doze and cyclic sleep states is provided.